Causing death by negligence (art. 104 of the criminal code): legal analysis (Journal of actual problems of jurisprudence, 2023)
The paper provides a legal analysis of the composition of causing death by negligence (Art. 104 of the Criminal Code). The author states the incalculable amount of this criminal offence for a long time in the republic, which determines its criminal-legal and criminological significance. The analysis showed that the investigative and judicial practice is still experiencing serious difficulties in qualifying this act, especially on subjective grounds. This is largely due to the unclear position of the Supreme Court of the Republic of Kazakhstan regarding the differentiation of certain crimes against human life and health, including causing death by negligence. This is largely due to the unclear position of the Supreme Court of the Republic of Kazakhstan regarding the differentiation of certain crimes against the life and health of a person, including causing death by negligence. In this regard, the author suggests: a) author's additions to Paragraph 27 and Paragraph 30 of the supreme judicial act of May 11, 2007; b) include in Art. 104 and Art. 114 of the Criminal Code a special composition providing for the responsibility of a person for improper performance of their professional duties, resulting in death or harm to the health of the victim. The scientific and practical significance of the article: ensuring the correct legal assessment of a criminal offence, improving the domestic criminal law and the practice of applying Art. 104 of the Criminal Code.Keywords: causing death, negligence, criminal law violation, qualification of the act, delineation.